Question Word in the Mandarin Language - Yunyu, Xu (LLT Journal: A Journal on Language and Language Teaching, 2013)
In an interrogative sentence in Mandarin language, a question word can be placed in the beginning, middle or end of a sentence. Because of the different nationand culture, when a foreign student learns Mandarin, they find it difficult to understandthe question words and the position of the question words in that language. Because ofthat, the writer proposes to explain such problems. This research aims to find out whatare the types of question words in Mandarin, and also to explain the function and usageof question words in the Mandarin interrogative sentence. An interrogative sentence isa very important sentence. In Mandarin, the following question words: ?(shu Who????(z n?li) where, ???(z n?er) where????(w shme) why, ??(z?nme) why????du? sh?o? how many???(du? ji?) how long????? (shme sh) when???(shme) what????(zushme) why?? ??(g shme) why???(gma) why and so on are used to ask who, where, what, how much, when, what time, and why. Those words havedifferent functions and usage.Each sentence has a certain structure and word order. A question word can beplaced in the beginning, middle, or end of a sentence. When the place is changed, thereis a possibility of miscommunication.